Equipment leasing in Malaysia: a new legal machinery - Ariffin, Razali (1985)
The writer's aim in writing this project paper is to study the application of leasing transaction in commercial industry Equipment leasing is a new area of law whereby it was introduced Malaysia in the late 1970's. Until then this type of transaction become more and. more popular among businessman especially, due to the fact that it enable them to lease expensive equipment without buying. In doing this comparison has to be made with other transactions especially Hire-Purchase transaction. Moreover the position of the lessee who has been declare bankrupt will be also discussed, to determine the status of the goods.